Management of Childhood - Onset Schizophrenia: A Literature Review - Ika Widyawati (HM Publisher, 2021)
Schizophrenia is one of the most common and well-known psychotic disorders that inhibits neurodevelopmental processes and has detrimental effects on cognitive, affective and social functions. Schizophrenia constitutes 1% of the general population, in the US there are more than 300.000 episodes of acute schizophrenia appearing per year. From epidemiolo.ical data on children and adolescents, it was found that less than 1/10.000 suffered from childhood schizophrenia, also found more in boys to adolescence, and the ratio was almost the same after adolescence as in adults. Early detection is needed so that schizophrenia that occurs especially in childhood does not develop into a chronic condition with a worsening prognosis.